Layanan Pelaksanaan Akad Nikah di Kantor Urusan Agama Medan Marelan (Studi Efektivitas dan Hambatannya pada masa Pandemi Covid-19) - Syahri, Alfi; Nasution, Mutiara; Putri, Aulia; Nur, Muhammad (STAI Serdang Lubuk Pakam, 2021)
This study aims to analyze the effectiveness and barriers to service implementation of the marriage contract during the Covid-19 pandemic at the Medan Marelan Religious Affairs Office. This study uses qualitative research methods, with a descriptive study approach. Data collection was done by interview, observation, and documentation study. Data analysis uses data reduction, data verification and drawing conclusions. Test the validity of the data using data triangulation and member check. The results showed that wedding services during the Covid-19 pandemic underwent significant changes and of course with government regulations there were obstacles in terms of service. Regarding administrative services, correspondence, such as requests, issuing letters, the public can do this by implementing health protocols. As for the implementation of marriages, the Office of Religious Affairs issued a circular regarding marriages that cannot be done with a large crowd, in the sense that only a few people will attend the wedding. The inhibiting factors for the effectiveness of these services include the lack of online service facilities, and the difficulty of accessing public information related to the policies of the office of religious affairs.